Illustrated Seamanship - Dedekam, Ivar, author (England : John Wiley & Sons, 2007)
Seamanship is the art of managing a boat. This book is a follow-up to the successful Sail & Rig Tuning and Illustrated Navigation covering knots, docking the boat and anchoring, all illustrated in Ivar Dedekam's distinctive style and backed up with clear and simple text.
Includes bibliographical references.
In English text.
Keywords: Seamanship; Yachting